Host–Microbe Interactions and Gut Health in Poultry—Focus on Innate Responses - Broom, Leon J. (Microorganisms, 2019)
Commercial poultry are continually exposed to, frequently pathogenic, microorganisms, usually via mucosal surfaces such as the intestinal mucosa. Thus, understanding host–microbe interactions is vital. Many of these microorganisms may have no or limited contact with the host, while most of those interacting more meaningfully with the host will be dealt with by the innate immune response. Fundamentally, poultry have evolved to have immune responses that are generally appropriate and adequate for their acquired microbiomes, although this is challenged by commercial production practices. Innate immune cells and their functions, encompassing inflammatory responses, create the context for neutralising the stimulus and initiating resolution. Dysregulated inflammatory responses can be detrimental but, being a highly conserved biological process, inflammation is critical for host defence. Heterogeneity and functional plasticity of innate immune cells is underappreciated and offers the potential for (gut) health interventions, perhaps including exogenous opportunities to influence immune cell metabolism and thus function. New approaches could focus on identifying and enhancing decisive but less harmful immune processes, improving the efficiency of innate immune cells (e.g., targeted, efficient microbial killing) and promoting phenotypes that drive resolution of inflammation. Breeding strategies and suitable exogenous interventions offer potential solutions to enhance poultry gut health, performance and welfare.